HADIS TENTANG IMBALAN MENGAJAR DAN HAL-HAL YANG TERKAIT DENGANNYA - Nursafitri, Riski (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2024)
Teaching is a noble occupation. Islam highly values people who have knowledge and practice it and teach it to others. By teaching, an educator will gain valuable experience as well as a good deed that can be reaped in the future. The purpose of this research is to find out the hadith related to rewards in teaching. The method used in this research is qualitative method by using literature study. The result of this study is that the reward of a teacher according to Surah Al Baqarah verse 263 allows as long as it does not hurt an educator by mentioning his gift.